Exclusion/Inclusion Based on Discrimination by Nationality in the Asylum Systems in Spain and Mexico - Torre Cantalapiedra, Eduardo; Gracia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
The management of the 2022 Ukrainian refugee crisis highlighted the need to critically examine the implementation of discriminatory international protection policies according to nationality. Through the analysis of statistical data, as well as the study and review of documents and literature, it discusses how exclusive or inclusive the Spanish and Mexican asylum systems are in terms of how states treat applicants differently according to their nationality. We argued that in both countries, institutional practices throughout the asylum process—access, procedure and resolution—discriminate on the basis of nationality, giving rise to various forms of exclusion and inclusion of refugees.
Keywords: asylum policies; discrimination; refugees; Spain; Mexico